Antisense Oligonucleotides: Concepts and Pharmaceutical Applications - Ariana Araya; David Arias; Karla Coto; María Rebeca López; Joselyn Rivera; Juan José Mora (Borneo Journal of Pharmacy, 2023)
Antisense oligonucleotides are drugs whose mechanism is based on binding to RNA target sequences. For this purpose, they modify the protein expression through steric hindrance and exon omission. Its production involves several steps: synthesis, purification, and lyophilization. Usually, the most complicated procedure is synthesis due to the chemical reactions necessary to add the required oligonucleotide bases. BP1001, inotersen, nusinersen, eteplirsen, and golodirsen are a few antisense drugs developed for treating neurodegenerative and neuromuscular diseases. Although antisense oligonucleotides present off-target reactions, multiple studies are being performed. The following review shows information regarding the pharmaceutical characteristics for industrial production and the current state of applicability in clinical practice. In conclusion, some molecules have already been approved for commercialization (inotersen, nusinersen, ataluren, eteplirsen, and golodirsen), showing them as promising therapeutic solutions in the short and medium term for disorders developed by specific genetic factors.